Soil Carbon Fractions from an Alluvial Soil Texture Gradient in North Carolina. Issue 5 (12th October 2017) - Deiss, Leonardo; Franzluebbers, Alan J.; Amoozegar, Aziz; Hesterberg, Dean; Polizzotto, Matthew; Cubbage, Frederick W.
Abstract : Core Ideas: Total, mineral‐associated, and mineralizable C fractions varied along a soil texture gradient. Specific surface area and Fe oxyhydroxides were positively associated with clay concentration. Soil C fractions were positively associated with surface area and Fe oxides. Aluminum oxide was not related to clay concentration or specific surface area. Mineralizable C had the most complex relationship with clay concentration. Soil texture is known to affect soil organic C (SOC) concentration and microbial activity, but these relationships are not always straightforward. We characterized total, mineral‐associated, and mineralizable C fractions along a gradient of soil texture within a flood plain field in the Coastal Plain region of North Carolina. Soil was collected from 0‐ to 5‐, 5‐ to 15‐, and 15‐ to 30‐cm depth intervals at 204 locations within a 7‐ha area. Samples were analyzed for soil particle size distribution, specific surface area (SSA), oxalate‐extractable Al and Fe to estimate short‐range‐ordered (i.e., poorly crystalline) oxyhydroxides, and soil C fractions. Overall, relationships among soil C fractions, textural classes, and depths were complex. Both SOC (0.4–13.9 g kg –1 soil) and mineral‐associated organic C (0–12 g kg –1 soil) increased as soil clay concentration increased (73–430 g kg –1 soil), but having two distinct slopes in each relationship with an inflection point of ∼150 g clay kg –1 soil at 0 to 5 and 5 to 15 cm and an inflection point of ∼250 g clay kg –1 soil at 15 to 30 cm. As clay concentration increased, SSA (12–76 m 2 g –1 soil) and oxalate‐extractable Fe (0.45–5.9 g kg –1 soil) also increased. A weaker relationship was observed between oxalate‐extractable Al (0.38–1.5 g kg –1 soil) and either SSA or mineral‐associated organic C. Mineralizable C increased with increasing clay concentration up until 143 ± 3, 152 ± 5, and 161 ± 11 g kg –1 (0–5, 5–15, and 15–30 cm, respectively), but decreased (0–5 and 5–15 cm) or stayed constant (15–30 cm) at higher clay concentrations. On the basis of untested observations, we surmise that binding of C to oxalate‐extractable Fe contributed to the accumulation of SOC and suppression of mineralizable C as the clay concentration increased. These results suggest that complex soil texture–physicochemical interactions underlie the inherent fertility of floodplain soils.